KINERJA PENDIDIK: TINJAUAN DARI KOMUNIKASI DAN MANAJEMEN KONFLIK (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract This study aims to identify and examine the correlation between communication headmaster with teachers performance, correlation between headmaster conflict management styles with teachers performance as well as communication and conflict management styles of headmaster with teachers performance at senior highschool in Tanah Putih Rokan Hilir. This research was conducted throughout senior highschool in Tanah Putih Rokan Hilir Riau. The population in this study are all teachers spread across 5 high schools in Tanah Putih Rokan Hilir Riau with totaling 142 teachers. Samples taken as many as 105 teachers. The instrument used to collect data for all variables by using questionnaire. Validity was tested using Pearson product moment formula. Instrument reliability coefficient calculated using Cronbach alpha. Result of analysis showing that there is is a positive correlation between communication headmaster with teacher performance. Partially, communications headmaster affect 91.6% value of teacher performance, communication headmaster will increase teacher performance. There is a positive correlation between conflict management style of headmaster with teacher performance. Partially, headmaster conflict management affects 87.8% value of teacher performance, headmaster conflict management headmaster will increase teacher performance. There is a positive correlation between headmaster communication and conflict management with the performance of teachers. Headmaster communication and conflict management together affect 93% value of teacher performance.Keywords: Headmaster communication, headmaster conflict management, teachers performance